Habits Related to Relaxation and Mindfulness of High School Students: Influence on Classroom Climate and Academic Performance [Hábitos Relacionados Con la Relajación y la Atención Plena (Mindfulness) en Estudiantes de Secundaria: Influencia en el Clim] - Oriol-Granado, X (Escuela Universitaria de Magisterio, 2016)
The objective of this study was to know the personal, family and school habits related to relaxation and mindfulness and to find out their impact, both in classroom climate and academic performance in adolescents. It also aims to check whether classroom climate has a mediating role in this relationship. The mean of academic performance at the end of the academic year, the Brief Questionnaire of Classroom Climate and the School Relaxation and Mindfulness Habits Brief Questionnaire, an instrument designed for the occasion, were used. The study was conducted with a sample of 420 students of Secondary Education and Baccalaureate in a high school centre. Results showed that personal and family relaxation/mindfulness habits predicted academic performance. This relationship was mediated by classroom climate. There were not statistical differences by gender in personal, family and school habits. © UPV/EHU.